Decrease of MtDNA copy number affects mitochondrial function and involves in the pathological consequences of ischaemic stroke. Issue 15 (5th July 2022) - Zhang, Zhaojing; Yang, Dongzhi; Zhou, Baixue; Luan, Yingying; Yao, Qihui; Liu, Yang; Yang, Shangdong; Jia, Jing; Xu, Yan; Bie, Xiaoshuai; Wang, Yuanli; Li, Zhihao; et al.
Abstract: The mtDNA copy number can affect the function of mitochondria and play an important role in the development of diseases. However, there are few studies on the mechanism of mtDNA copy number variation and its effects in IS. The specific mechanism of mtDNA copy number variation is still unclear. In this study, mtDNA copy number of 101 IS patients and 101 normal controls were detected by qRT‐PCR, the effect of D‐loop variation on mtDNA copy number of IS patients was explored. Then, a TFAM gene KD‐OE PC12 cell model was constructed to explore the effect of mtDNA copy number variation on mitochondrial function. The results showed that the mtDNA copy number level of the IS group was significantly lower than that of the normal control group ( p  < 0.05). The relative expression of TFAM gene mRNA in the cells of the OGD/R treatment group was significantly lower than that of the control group ( p  < 0.05). In addition, after TFAM gene knockdown and over‐expression plasmids were transfected into HEK 293T cells, mtDNA copy number and ATP production level of Sh‐TFAM transfection group was significantly decreased ( p  < 0.05), while mtDNA copy number and ATP production level of OE‐TFAM transfected group were significantly higher than that of blank control group and OE‐ctrl negative control group ( p  < 0.01). Our study demonstrated that mitochondrial D‐loop mutation and TFAM gene dysfunction can cause the decrease of mtDNA copy number, thus affecting the mitochondrial metabolism and function of nerve cells, participating in the pathological damage mechanism of IS.